1994
DOI: 10.1039/c39940000625
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific binding of chemically modified salen-type Schiff base complexes of copper(II) with DNA [salen = bis(salicyclidene)ethylenediamine]

Abstract: DNA-fi bre ESR measurements reveal that the orientation of water-soluble cationic salen-type Schiff base complexes of copper(ii) on DNA changes by modification of the bridging group between two imino nitrogens in the complex; the 1,2-phenylenediamine and 2,3-naphthalenediamine bridges enable the complex to intercalate to DNA, while the et h y lenedia m i ne bridge i nd uces g roove bi nd i ng .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…1) were synthesized [21] by the reaction of 5-(triethylammoniummethyl)salicylaldehyde chloride, 1,2 phenylendiamine and copper(II) or zinc(II) acetate in a 2:1.1:1 molar ratio, in doubly distilled water, and isolated as perchlorate salts. The 5-(triethylammoniummethyl) salicylaldeide chloride ligand was prepared from 5-chloromethyl salicylaldeide [28] and triethylamine in THF.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) were synthesized [21] by the reaction of 5-(triethylammoniummethyl)salicylaldehyde chloride, 1,2 phenylendiamine and copper(II) or zinc(II) acetate in a 2:1.1:1 molar ratio, in doubly distilled water, and isolated as perchlorate salts. The 5-(triethylammoniummethyl) salicylaldeide chloride ligand was prepared from 5-chloromethyl salicylaldeide [28] and triethylamine in THF.…”
Section: Methodsmentioning
confidence: 99%
“…ESR measurements on DNA-fibres [21] have revealed that the orientation of water-soluble cationic Salen-type Schiff base complexes of copper(II), relative to the DNA axis, changes by modification of the chain length bridging the two imino nitrogens in the complex. Such measurements allowed to conclude that the 1,2-phenylenediamine bridge enables the metal complex to intercalate DNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of interaction of Cu(II) Schiff bases with DNA has been extensively investigated. It has been shown that the mode of binding of the metal complex to DNA depends on the substituent in the phenyl ring as well as on the nature of diamine used for forming the Schiff base [16]. Griffin and coworkers have investigated DNA binding/cleaving properties of 26 salen complexes of Mn(III) in the presence of terminal oxidants using DNA affinity cleaving techniques and found that DNA cleaving efficiency varies with both the structure and stereochemistry of the bridging substituent [17].…”
Section: Introductionmentioning
confidence: 99%
“…19 Sato et al reported stereospecific binding of chemically modified Salen-type Schiff-base complexes of copper(II) with DNA by ESR technique, and found the substitution of the phenylene or naphthalene bridging group for the ethylene group transforming the complexes from groove binders to intercalators. 20 Bhattacharya et al reported a new water-soluble Co-salen complex that can cleave DNA spontaneously under ambient aerobic conditions. The cleavage is further enhanced by including dithiothreitol in the reaction buffer.…”
mentioning
confidence: 99%